Natural quantum operational semantics with predicates - Sawerwain, Marek; Gielerak, Roman (Zielona Góra: Uniwersytet Zielonogórski)
A general definition of a quantum predicate and quantum labelled transition systems for finite quantum computation systems is presented. The notion of a quantum predicate as a positive operator-valued measure is developed. The main results of this paper are a theorem about the existence of generalised predicates for quantum programs defined as completely positive maps and a theorem about the existence of a GSOS format for quantum labelled transition systems. The first theorem is a slight generalisation of D'Hondt and Panagaden`s theorem about the quantum weakest precondition in terms of discrete support positive operator-valued measures.
Keywords: quantum computation; predicate notion for quantum programs; quantum labelled transition systems